2020
DOI: 10.3390/diagnostics11010049
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography for the Assessment of Pulmonary Hypertension and Congenital Heart Disease in the Young

Abstract: While invasive assessment of hemodynamics and testing of acute vasoreactivity in the catheterization laboratory is the gold standard for diagnosing pulmonary hypertension (PH) and pulmonary vascular disease (PVD) in children, transthoracic echocardiography (TTE) serves as the initial diagnostic tool. International guidelines suggest several key echocardiographic variables and indices for the screening studies when PH is suspected. However, due to the complex anatomy and special physiological considerations, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 175 publications
(299 reference statements)
0
10
0
Order By: Relevance
“…Our data demonstrate that readily available transthoracic echocardiography (25,28) can sufficiently document the post-LuTx improvements of RVH, RV dilation, and LV filling. In this regard, we unraveled the RV/LV end-systolic diameter ratio (29,30), LV end-systolic eccentricity index (LVES EI) (31,32), and RV end-systolic remodeling index (RVES RI) (33) as the most robust and useful echocardiographic markers (25,28,30,34). We (29) and others (31,35) showed that children with more than mild PH had increased RV/LV endsystolic dimension ratio (>1) that reached a grossly abnormal ratio of 2.6 pre-LuTx in the end-stage PAH children of the current study (Figure 1E,F).…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that readily available transthoracic echocardiography (25,28) can sufficiently document the post-LuTx improvements of RVH, RV dilation, and LV filling. In this regard, we unraveled the RV/LV end-systolic diameter ratio (29,30), LV end-systolic eccentricity index (LVES EI) (31,32), and RV end-systolic remodeling index (RVES RI) (33) as the most robust and useful echocardiographic markers (25,28,30,34). We (29) and others (31,35) showed that children with more than mild PH had increased RV/LV endsystolic dimension ratio (>1) that reached a grossly abnormal ratio of 2.6 pre-LuTx in the end-stage PAH children of the current study (Figure 1E,F).…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that readily available transthoracic echocardiography ( 2 , 37 ) can sufficiently document the post-LuTx improvements of RV-hypertrophy, RV dilation, and LV filling. In this regard, the RV/LVes ratio ( 10 , 38 ), the LVes EI ( 26 , 39 ), and RV endsystolic remodeling index ( 9 ) are robust and useful echocardiographic markers ( 2 , 11 , 37 , 38 ). Moreover, the LV EI and RV/LV dimension ratio were associated with a lower WHO functional class, and worse hemodynamics ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we provide normal reference values and percentiles (of the RV/LVes ratio and LVes EI in healthy children and adolescents (1 day–18 years) that will assist to identify children with abnormal values. The RV/LVes ratio and the LVes EI have been shown to be useful, simple, reliable, and non-invasive markers of right ventricular hypertension in infants with PH ( 11 , 12 , 19 , 36 , 40 ) and may be incorporated in routine protocols when there is a concern for PH in children.…”
Section: Discussionmentioning
confidence: 99%
“…While the M-mode measurement and use of the Teichholz formula is based on the assumption of an ellipsoid geometrical structure of the left ventricular cavity, this measurement can be flawed. Particularly in conditions where the geometrical structure of the left ventricle is altered, either due to morphological changes due associated congenital heart disease, previous surgery, abnormal wall motion (abnormal conduction) or in PH with significant septal shift towards the left ventricle, the geometrical shape of the left ventricular cavity is changed (31,(79)(80)(81). For quantitative measure of left ventricular function, the modified Simpson formula can be used, as described elsewhere.…”
Section: The Left Ventricle and Ventricular-ventricular Interactions (Vvi) In Phmentioning
confidence: 99%